(untitled) (Global Journal of Human-Social Science, 2013)
The purpose of the present study was to find out the prevalence and psychological correlates of abnormal eating attitudes in female college students in the city of Chennai, Tamil Nadu. Two hundred undergraduates with mean age 19.0 years from five premiere colleges affiliated to the University of Madras were administered the Eating Attitudes Test (EAT-26), Rosenberg Self Esteem Scale, State Trait Anxiety Inventory and Beck Depression Inventory. Abnormal eating attitudes (EAT-26 score ≥ 20) were found in 30% of the total sample. Use of Pearson Correlation and independent t-test revealed that participants who had abnormal eating attitudes had scored higher levels of depression and higher levels of both state as well as trait anxiety than those with normal eating attitudes ( Eat-26 score